lncRNA GAPLINC regulates vascular endothelial cell apoptosis in atherosclerosis - Jun Pan; Bing Wang; Xibin Pu; Chenyang Qiu; Donglin Li; Ziheng Wu; Hongkun Zhang; Yangyan He (Archives of Medical Science, 2023)
Introduction In this study, we investigated the role of the long non-coding RNA GAPLINC in atherosclerosis under oxidized low-density lipoprotein (ox-LDL) treatment.